Igualdade e não discriminação de gênero contra as mulheres no direito internacional dos direitos humanos: análise da jurisprudência consultiva interamericana - Prata, Ana Rita Souza (2019)
This work aims to demonstrate that the structural gender inequality can be (and actually is) reinforced or confronted by means of the Human Rights International Law. Firstly, in investigates who is the subject woman, how it was constructed and how it have occupied from the beginning a subordinated place in society. This study is necessary because, without gender and, even, intersectionality perception, the potencial emancipatory devices cannot achieve their goals. The study focus on the Human Rights guarantee systems, and is analysis frame the consultive opinions produced by the Interamerican Court of Human Rights concerning the principle of equality and gender non-discrimination against women. The research carries on a critical and gender biased, intersectional and feminist, analysis of consultive opinions, followed by a comparison of concrete cases approached by Brazilian Law system. Concluding, what is noticeable is the potenciality of those devices, which should be internally fullfiled, such as the norms and other conventional jurisprudences, aiming to confronte the gender violences suffered in a daily basis by women